The double-edged sword of inflammation in inherited retinal degenerations: Clinical and preclinical evidence for mechanistically and prognostically impactful but treatable complications - Sarici, Kubra; Vyas, Aanal; Iannaccone, Alessandro (Frontiers in Cell and Developmental Biology, 2023)
We present retrospective data stemming from our clinical research efforts of the past several years alongside a review of past and current clinical and preclinical data brought about independently by a number of investigators supporting our clinical evidence for the importance of inflammation in inherited retinal degenerations (IRDs). We show how inflammation is a complicating factor in IRDs but, if recognized and managed, also a great opportunity treatment-wise to mitigate disease severity immediately, improve patient prognosis and quality of life, extend the treatment windows for gene specific and agnostic therapeutic approaches, mitigate the impact of inflammatory complications on the accurate estimate of vision changes in IRD natural history studies, improve the chances of safer outcomes following cataract surgery, and potentially reduce the likelihood of inflammatory adverse events and augment the efficacy of viral vector-based treatment approaches to IRDs.